Signaling and Dynamics of Activation of LFA-1 and Mac-1 by Immobilized IL-8 - Lomakina, Elena B. (2010)
The dynamic response of neutrophils to interleukin-8 (IL-8) is of central interest in inflammation. Chemokine –induced β(2) integrin dependent adhesion can take several minutes after initial contact with IL-8 as evidenced by increased cell adhesion to intracellular adhesion molecule 1 (ICAM-1). The goal of this study is to identify signaling events that are critical for this response. We demonstrate that neither the PI3K inhibitor wortmannin, nor the PKC inhibitor bisindolymaleimide had any effect on IL-8 induced adhesion to ICAM-1. However, inhibition of PLC with U73122 or stopping the release of intracellular calcium by its downstream effector IP3 with caffeine or 2-aminoethoxydiphenyl borate completely blocked the adhesive response. Chelation of intracellular calcium with BAPTA or extracellular calcium with EGTA completely abrogated neutrophil adhesion to ICAM-1. This adhesion is mediated by LFA-1 (α(L)β(2)) within first 300 seconds after chemokine stimulation, followed by Mac-1 (α(M)β(2)) mediated adhesion, beginning 350 seconds after stimulus. Inhibition of p38MAP kinase results in a time course similar to Mac-1 inhibition, consistent with published evidence that Mac-1 mediated adhesion is p38MAP kinase dependent. These findings confirm a PLC dependent, PKC independent pathway from chemokine stimulus to integrin activation previously identified in other cell types, and demonstrate distinct dynamics and different requirements for LFA-1 vs. Mac-1 activation in primary human neutrophils.